2018
DOI: 10.1016/j.stem.2018.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Regeneration of Large Vessels Is a Biphasic Process Driven by Local Cells with Distinct Proliferative Capacities

Abstract: The cellular and mechanistic bases underlying endothelial regeneration of adult large vessels have proven challenging to study. Using a reproducible in vivo aortic endothelial injury model, we characterized cellular dynamics underlying the regenerative process through a combination of multi-color lineage tracing, parabiosis, and single-cell transcriptomics. We found that regeneration is a biphasic process driven by distinct populations arising from differentiated endothelial cells. The majority of cells immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
160
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(189 citation statements)
references
References 34 publications
13
160
0
Order By: Relevance
“…This is consistent with the observation that the transplant vasculature in humans undergoes alloimmune injury along the length of the arterial tree, from artery to the microvasculature (4). Recent work identifies reparative endothelial progenitor cells embedded in the mouse aortic endothelium, but repair from mechanical injury involved EC dedifferentiation and proliferation (34). We confirmed that apelin expression in human heart explant coronary artery endothelium was induced versus unutilized donor arteries, but these specimens had advanced disease with heterogeneous expression of the biomarkers, and may not all reflect evolving lesions.…”
Section: Discussionsupporting
confidence: 62%
“…This is consistent with the observation that the transplant vasculature in humans undergoes alloimmune injury along the length of the arterial tree, from artery to the microvasculature (4). Recent work identifies reparative endothelial progenitor cells embedded in the mouse aortic endothelium, but repair from mechanical injury involved EC dedifferentiation and proliferation (34). We confirmed that apelin expression in human heart explant coronary artery endothelium was induced versus unutilized donor arteries, but these specimens had advanced disease with heterogeneous expression of the biomarkers, and may not all reflect evolving lesions.…”
Section: Discussionsupporting
confidence: 62%
“…15,16 Beside the risk for thrombus development, which was the focus of a previous study, 11 the further process and changes of the intimal lesion itself is consistently topic of research. [17][18][19][20][21] Most remarkable observation during our study was the determination of a clear trend in reduction of defect sizes 7 days after defect creation. Mean shrinkage was calculated 42.8%, absolute decrease in size was 0.75 mm 2 on average.…”
Section: Discussionsupporting
confidence: 53%
“…However, based on the literature that reendothelialization of arteries, endothelial proliferation (39), and reduced atherosclerosis (21) is linked to CXCR4 expression and function, we argue that CXCR4 itself has a protective role. Additional recent RNA sequencing data analysis of locally regenerating ECs to recover from endothelial injury in vivo shows enhancement of CXCR4 expression (45). Endothelial CXCR4 is also reported to be athero-protective through attenuating vascular permeability by enhancing VE-cadherin expression and stabilizing VE-cadherin complexes (21).…”
Section: Discussionmentioning
confidence: 99%